Theorie und Systematik materialer Textkulturen Abschlussband des SFB 933 - Dietrich, Nikolaus; Lieb, Ludger; Schneidereit, Nele (Materiale Textkulturen, 2023)
The final volume in the series synthesizes the research conducted by the Heidelberg Collaborative Research Center 933. Systematized into six topic areas (reflecting on writing, layout and text/image, memory and the archive, material transformation, sanctification, and rule and administration), the CRC scholars summarize the knowledge gained from twelve years of interdisciplinary work into 35 theses on a theory of material text cultures.